2012
DOI: 10.1097/ccm.0b013e318243168e
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance cultures of methicillin-resistant Staphylococcus aureus as a tool to predict methicillin-resistant S. aureus ventilator-associated pneumonia*

Abstract: In our study, prior methicillin-resistant S. aureus colonization as ascertained by once-weekly active surveillance culture yielded high specificity and negative predictive value, suggesting that negative active surveillance culture can accurately exclude methicillin-resistant S. aureus as an etiology in most patients with ventilator-associated pneumonia and may decrease the need for empirical methicillin-resistant S. aureus coverage in patients with suspected ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Results similar to ours were recently obtained in a prospective observational study 16 of 388 medical and surgical ICU patients with ventilator-associated pneumonia (VAP). In that study, 37 patients had 5%); most of the patients (3.8% of the total cohort) had pneumonia.…”
Section: Discussionsupporting
confidence: 71%
“…Results similar to ours were recently obtained in a prospective observational study 16 of 388 medical and surgical ICU patients with ventilator-associated pneumonia (VAP). In that study, 37 patients had 5%); most of the patients (3.8% of the total cohort) had pneumonia.…”
Section: Discussionsupporting
confidence: 71%
“…Chan et al [17] reported that active surveillance culture from multiple sites can accurately exclude MRSA as an etiology in most patients with ventilator-associated pneumonia. This observation is consistent with the results presented here; however, differences in the diagnostic value for each anatomic site were not investigated in that study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, active surveillance for MRSA is recommended in ICU patients [12], though no consensus has been reached regarding which site to use for optimal detection due to limited data [13][15]. Moreover, only a few studies have evaluated the predictive value of surveillance culture for subsequent MRSA infections in ICU patients [16], [17], with no study directly comparing the predictive values based upon surveillance culture site.…”
Section: Introductionmentioning
confidence: 99%
“…Plumb and Miller for their interest in our article (1). Plumb and Miller for their interest in our article (1).…”
Section: The Authors Replymentioning
confidence: 99%